THE STRUCTURIZATION OF METALS SURFACE UNDER INFLUENCE OF PULSE PLASMA FLOWS - Zhukeshov, A.M.; Gabdullina, A.T.; Pak, S.P.; Amrenova, A.U. (Recent Contributions to Physics, 2018)
The phase structure of a carbon steel surface, modified by plasma processing in various modes, by the X-ray analysis method is investigated. The modes of unitary and repeated influence by pulse flows of plasma are used. The influence of the sizes of dispersion coherent areas belonging to various phases, on microhardness of steel is investigated. Is shown, that the hardness of the processed steel increases proportionally to decreasing of the ferrite crystallite sizes at unitary influence. At repeated influence the greatest ratio of the modified phase contains in a sample subjected 10 multiple processing. As a result of updating structure of metal are formed crystalline with the sizes 10-20 nm.